#TITLE_ALTERNATIVE# - TANUJAYA (NIM 13503104), ALLENTINE
People nowadays have a weaker and older brain capibility than their actual ages. It happens because most people only use 10 % of their brain and leave 90 % idle. By training the brain continually, the brain capibility can be improved. One of the methods to improve the brain capability is by using technology that help people, which is Brain Computer Interface (BCI). This technology can help user to communicate directly with computer without needing any physical movement. So only the electric signal of the brain is required. BCI can be used as support technology which connects the ability gap between human and environment, for example BCI can help a person with impaired vision to see. With this kind of technology, the brain capability of this particular group of people can be improved. With this condition, the goal of this final project is to design an interaction system model which improve the brain capability of people with impaired vision who use BCI, by improving the ability to memorize, analyze, think, calculate, identify, and speak (verbal or linguistic). The improvement of brain capability use training model from Train Your Brain DR Kawashima and psychology test. This system can also be used by normal people despite the target of its development being people with impaired vision who use BCI. The interaction design method in this final project is a new paradigm in the system design by focusing on user (user-centred design) and usability aspect. The design is made by using task analysis and task design concepts. The interaction design is also illustrated in interaction scenario model which shows how the system works and interacts with its user. The result of this final project are the design of B3TS interaction model and scenario model simulation which represent system design and its interaction.